Development and characterization of functional beverage based on soursop (Annona muricata L.), inulin, and whey powders - S. Fernández-Huazo; I.I. Ruiz-López; C.E. Ochoa-Velasco; P. Hernández-Carranza (Applied Food Research)
This study aimed to develop and evaluate ''functional'' beverages made from a blend of soursop (Annona muricata L.), whey, and/or inulin using a selected Lactobacillus strain. To achieve this objective, various steps were conducted: 1) analysis of soursop powder in its chemical proximal, physicochemical, and antioxidant properties, 2) selection of Lactobacillus species with the highest ability to grow in a formulated beverage, 3) evaluation of several beverages based on soursop, whey, and/or inulin in their physicochemical characteristics, antioxidant capacity, probiotic survival, and sensory acceptance to choose the one with the highest quality characteristics, 4) analyze the effect of storage time (20 days at 4 °C) on the quality characteristics of chosen beverage. The results indicated that soursop contains functional compounds like dietary fiber (2.41%), total phenolic compounds (370.26 mg GAE/100 g), and antioxidant capacity (2260.72 mg Trolox/100 g). Although LAB grew (6.88–7.73 log cycles) in formulated beverage, L. acidophilus presented the highest microbial count (7.73 log cycles, p < 0.05) after 12 h of fermentation; therefore, it was used to ferment soursop solutions. On the other hand, among fermented beverages, the one formulated with soursop, whey, and inulin presented the highest probiotic growth and antioxidant capacity. Therefore, it was analyzed during the storage at 4 °C. After storage time, the fermented beverage maintained a high probiotic count (> 7.5 log cycles) and antioxidant capacity (even more than at the beginning of storage), with a good sensory acceptance (like it). Thus, this study successfully developed a probiotic beverage using soursop, whey, and inulin, which have favorable functional properties and sensory acceptance.